2016
DOI: 10.1097/mbc.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran etexilate versus low-molecular weight heparin to control consumptive coagulopathy secondary to diffuse venous vascular malformations

Abstract: Diffuse venous malformations can be associated with a consumptive coagulopathy characterized by a reduction of fibrinogen level, platelet count and elevated D-dimer level. We report a case of a patient with extensive venous malformations, hemorrhagic symptoms and biological signs of intravascular coagulopathy. She was initially treated effectively with low-molecular weight heparin (LMWH) (enoxaparin 1 mg/kg, bid) and switched to low-dose dabigatran etexilate (110 mg bid) for more than 2 years. Both treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Whilst many authors agree that anti‐coagulation therapy should be administered peri‐procedurally for LIC patients and in those with significant thrombo‐emboli risk, the exact threshold for instigation and the clinical efficacy of these treatments in preventing complications are still unknown. A regime of LMWH 10 and 20 days, pre‐ and post‐procedure respectively, to prevent haemorrhagic complications in VM patients has been suggested .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst many authors agree that anti‐coagulation therapy should be administered peri‐procedurally for LIC patients and in those with significant thrombo‐emboli risk, the exact threshold for instigation and the clinical efficacy of these treatments in preventing complications are still unknown. A regime of LMWH 10 and 20 days, pre‐ and post‐procedure respectively, to prevent haemorrhagic complications in VM patients has been suggested .…”
Section: Introductionmentioning
confidence: 99%
“…There are case reports of oral anti‐Xa agents being used for severe LIC in adults . The use of an oral agent avoids the need for injections and is thus appealing for children.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that other oral anti Xa (DABIGATRAN) was effective in treatment of VM venous thrombosis. 14 Our study underline that RIVAROXABAN, despite the lack of recommendation, is used in daily practice in VM thrombosis, but more date are needed to recommend antiXa treatment in VM thrombosis.…”
Section: Discussionmentioning
confidence: 84%
“…First, painful flareups may be associated with aggravation of those hematologic parameters associated with LIC and therefore conservative (eg, compression garments) or medical treatment directed to this portion of the coagulation cascade, that is, low molecular-weight heparin (LMWH) or direct anti-Xa agents may control and improve patient symptoms. 12,14,[18][19][20][21] Second, patients with coagulopathy are more likely to develop painful phleboliths, thrombophlebitis, deep venous thrombosis, and pulmonary embolism and therefore must be identified to allow appropriate thromboprophylaxis. 15,17 Third, and most importantly to the interventional radiologist, minor sclerotherapy among other factors can cause LIC to rapidly progress onto disseminated intravascular coagulation (DIC) either intra-or postprocedurally with life-threatening consequences.…”
Section: Addressing Critical Preprocedures Hematologic Concernsmentioning
confidence: 99%
“…13,23,24 Similar risk factors in the setting of an elevated d-dimer and either decreased fibrinogen or chronic pain may be an indication for chronic LMWH or direct oral anticoagulants (DOACs) such as dabigatran or rivaroxaban, however, should always be managed in consultation with a hematologist. 17,20,21 In cases of intervention in KTS or CLOVES, one may consider temporary IVC filter placement (Table 2). 25 Once the patient workup is thought to be complete prior to an intervention, one may consider reviewing a checklist to ensure all matters have been addressed (Table 3).…”
Section: Addressing Critical Preprocedures Hematologic Concernsmentioning
confidence: 99%